Hurrell Froude and the Reformers - Baker, William J. (The journal of ecclesiastical history, 1970)
‘No portion of our annals’, Macaulay wrote in 1828, ‘has been more perplexed and misrepresented by writers of different parties than the history of the Reformation’. In the early years of the nineteenth century, when polemicists turned to history more often than to philosophy or theology, the Reformation was the subject most littered with the pamphlets of partisan debate. Macaulay could have cited numerous examples. Joseph Milner's popular History of the Church of Christ (1794–1809) set the Reformation in sharp contrast to the ‘Dark Ages’ when only occasional gleams of evangelical light could be detected, thus providing the Evangelical party with a historic lineage; Robert Sou they, in his Book of the Church (1824), presented a lightly-veiled argument for the retention of the existing order of Church and State as established in the sixteenth century; and in 1824 William Cobbett began the first of his sixteen weekly instalments on a history of the Protestant Reformation in England and Ireland, in order to call attention to the plight of labourers in the British Isles. In the history of the Reformation, duly manipulated (‘rightly interpreted’), men found precedents for their own positions and refutation of their opponents' arguments.